Comparison of Serum Vitamin C Levels Between Pulmonary Tuberculosis and Healthy Controls in Medan - Rizka Helmi; Bintang Yinke Magdalena Sinaga; Parluhutan Siagian; Putri Eyenoer (Jurnal Respirologi Indonesia, 2022)
Background: Pulmonary tuberculosis infection is a high burden, especially in developing country. Vitamin C is a water-soluble micronutrient that contributes to immune defense by supporting avarietyof innate and adaptive immunity. Vitamin C protects the host from reactive oxygen and reactive nitrogen intermediates generated during Mycobacterial infection. Pulmonary tuberculosis patients have lower vitamin C levels because Mycobacterium tuberculosis infection produces reactive oxygen species for replication as well asmetabolism and also because of reduced nutrient intake. Vitamin C as an antioxidant also plays role in killing Mycobacterium tuberculosis by encouraging Fenton reaction.Methods: This is a case control study of serum vitamin C levels in pulmonary tuberculosis patients and healthy controls. Vitamin C levels were measured by ELISA (Enzyme Linked Immunosorbent Assay).Results: The number of subjects was 40 people, divided into 20 subjects of pulmonary tuberculosis as cases and 20 healthy controls, aged between 18–65 years old. Vitamin C levels according to age group were 99.03±38.60 ng/ml and 80.53±27.38 ng/mlfor18–30 years, 84.85±49.69 ng/ml and 82.70±14.93ng/ml for31–40 years, 61.34±25.36 ng/ml and 79.93±22.81 ng/ml for41–50 years, 71.43±18.36 ng/ml and 78.69±54.21 ng/ml for51–65 years. Vitamin C levels of male subjects based on case and control groups were 88.11±42.07 ng/ml and 78.36±28.95 ng/ml while for the female were 73.20±11.56 ng/ml and 83.16±23.77 ng/ml. Mean vitamin C levelin pulmonary tuberculosis patients was 83,64±35,99 ng/ml and in healthy controls was80,22±26,44 ng/ml.Conclusion: There was no significant difference in vitamin C levels between pulmonary tuberculosis patient and healthy people.